A inserção internacional da China no pós Guerra Fria - Shu, Silvana Shiow Shyan (2006)
Considering the contemporary international system, this study aims to examine China s international engagement process by analyzing the importance of domestic factors and external factor in China foreign policy. The changes in China have transformed every aspect of its relationship with the outside world. Regarding to the domestic factors, they are mainly concentrated on Chinese interests which is its development. In the other hand, the external factors are basically concentrated on the relations among China and USA. This issue is followed by a discussion of the implications of United States in China s international engagement. As part of this study, it s aimed to examine the main adaptations of American Foreign Policy in post Cold War. American policy must display a sense of priorities which is keeping its role as the most powerful actor in the international order. Furthermore, as part of its strategy, the United States will address efforts to handle a workable and sustainable foreign policy with China. China is increasingly shaping international relations by its new role in the world and its rise. Therefore, it is very important to analyze the process of China s international engagement in the post Cold War era